Evaluation of the neurotoxic effects of intrathecal administration of (S)-(+)-Ketoprofen on rat spinal cords: randomized controlled experimental study - Kaya,Cengiz (2019)
Abstract Background and objectives Intrathecal administration of non-steroidal anti-inflammatory drugs is more efficacious for post-operative pain management. Cyclooxygenase inhibiting non-steroidal anti-inflammatory drugs like (S)-(+)-Ketoprofen, may be effective at lower intrathecal doses than parenteral ones. Preclinical safety regarding possible neurotoxicity associated with the intrathecal (S)-(+)-Ketoprofen was not evaluated. Here we analysed the neurotoxicity of intrathecally administered (S)-(+)-Ketoprofen in rats. Methods A randomized placebo-controlled experimental study was conducted. Sprague-Dawley rats (250-300 g) aged 12-16 weeks were randomly divided into 2 treatments [100 and 800 µg (S)-(+)-Ketoprofen] and control (sterile water) groups. Intrathecal catheters were placed via the atlantoaxial space in anesthetized rats. Pinch-toe tests, motor function evaluations and histopathological examinations of the spinal cord and nerve roots were performed at days 3, 7 and 21. Spinal cord sections were evaluated by light microscopy for the dorsal axonal funiculus vacuolation, axonal myelin loss, neuronal chromatolysis, neuritis, meningeal inflammation, adhesions, and fibrosis. Results Rats in all the groups exhibited normal pinch-toe testing response (score = 0) and normal gait at each observed time (motor function evaluation score = 1). Neurotoxicity was higher with treatments on days 3 and 7 than that on day 21 (2, 3, 0, p = 0.044; 2, 5, 0, p = 0.029, respectively). On day 7, the total scores reflecting neuronal damage were higher in the 800 µg group than those in the 100 µg and Control Groups (5, 3, 0, p = 0.048, respectively). Conclusion Intrathecal (S)-(+)-Ketoprofen caused dose-dependent neurohistopathological changes in rats on days 3 and 7 after injection, suggesting that (S)-(+)-Ketoprofen should not be intrathecally administered.